Offshore blowouts : causes and control - Holand, Per (Gulf Pub. Co., 1997)
This book, based on the SINTEF Offshore Blowout Database, thoroughly examines U.S. Gulf of Mexico and Norwegian and UK North Sea blowouts that occurred from 1980 to 1994. This book reveals the operations that were in progress at the onset of the blowouts and helps you learn from the mistakes of others.